Conflicting Visions of War: Winston Churchill and Rudyard Kipling’s Evocation of the Boer War - Laïli Dor (Cahiers Victoriens et Edouardiens)
Rudyard Kipling and Winston Churchill both covered the Boer War as newspaper correspondents, working respectively for the Friend of the Free State and the Morning Post, and in later days, both authors looked back on the Boer War in their autobiographies. Kipling devoted a chapter of his autobiography Something of Myself to his experience of the war, while Churchill described his adventures, including his spectacular escape from a Boer prison in My Early Years. Kipling also devoted several short stories to the subject, two of which (“A Sahib’s War” and “The Captive”, both published in Traffics and Discoveries in 1904) offer an interesting complement to his autobiographical account. Kipling and Churchill witnessed the war in fairly similar conditions, observing the fighting at close range and enjoying friendly contact with British soldiers. Yet this common experience resulted in opposite visions and discourse: Churchill presented the Boers as loyal enemies, to be fought but respected. Kipling, on the contrary, saw them as treacherous guerrillas who deserved due punishment, and he heavily emphasized the threat they represented to the British Empire. The purpose of this article is to analyse these conflicting accounts of a single event, taking into account the authors’ experiences and the readership they were writing for, in order to show how ideological discourse is elaborated through the rhetorical use of historical facts.